PERAN BRAND AMBASSADOR DAN E-WOM DALAM MEMPENGARUHI MINAT PEMBELIAN PRODUK MS GLOW MEN DI SUMBAWA BESAR - Haryadi, Wahyu; Karmita, Putri (Samalewa: Jurnal Riset & Kajian Manajemen, 2024)
This study aims to determine the role of brand ambassador and electronic word of mouth (e-WoM) on influenceting interest in buying MS. Glow Men products in Sumbawa Besar. The type of this study was causal associative study which is used to examine the effect of brand ambassadors and Electronic Word of Mouth (e-WoM) on interest in buying MS. Glow Men products in Sumbawa Besar. The type of data used in this study was quantitative data obtained directly from respondents using a questionnaire. The respondents in this study were all 50 customers who had buyed MS Glow Men skincare in Sumbawa Besar. The sample determination in this study was based on a non-probability sampling technique using the accidental sampling method. The all of data used in this study was processed using the SPSS program, to be studied and analyzed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination test (R2). The results of this study showed that brand ambassadors and Electronic Word of Mouth (e-WoM) had a positive and significant effect on interest in buying MS. Glow Men product in Sumbawa Besar, either partially and simultaneously. The ability of the brand ambassador and Electronic Word of Mouth (e-WoM) variables to explain variations in changes in the variable interest in buying MS. Glow Men product in Sumbawa Besar was 16.5%, while the remaining of 83.5% was effected by other factors outside this research model, such as perceived convenience, promotion and price.